A new treatment for ingrown toenail with CO2 laser: a retrospective study - Ganggang Li; Xuejing Tan; Yuxin Hui; Xiaoqiang Li; Dan Han; Yanli Yuan; Huiqun Ma (Taylor & Francis Group, 2024)
Background There are various surgical treatments on ingrown toenails. However, the treatment without matricectomy, damaging the nail and not operating on the nail bed could be better.Objective To present a new treatment for ingrown toenail that completely preserve the nail and nail matrix.Methods 52 surgical procedures were performed on 47patients with ingrown toenail who applied to Dermatology Department from May 14th, 2021 to March 12th, 2023 were enrolled. A certain volume of soft tissue surrounding the lesion was ablated under local anesthesia.Results 52 surgical procedures were performed on 47patients. All lesions' results were excellent except 3 with relapse (the cure rate is 94.23%). These cases healed after retreatment. During the minimum of 1 year follow-up, the cosmetic effect was remarkable with normal appearance and function. The mean operative time was 9.83 ± 2.24 min. There were no complications was observed. The mean time for patients returning to walk was1.36 ± 0.49 days.Conclusion This study demonstrates that ingrown toenail can be surgically treated without matricectomy and preserved the nail. All necrotic tissue and certain volume of soft tissue surrounding the lesion should be ablated to decompress the nail and reduce inflammation.